(untitled) (El-Wahat Journal for Research and Studies, 2023)
ملخص: هدفنا من خلال هذه الدراسة إلى إلقاء الضوء على مفهوم رأس المال النفسي بإعتباره من بين المفاهيم الحديثة في مجال السلوك التنظيمي الإيجابي، وقد حاولنا من خلال إتباعنا لخطوات المنهج الوصفي تقديم تعريف لمفهوم لرأس المال النفسي، كما تطرقنا إلى نشأته وتطوره، ومكوناته، وكذا الدور الذي يلعبه في تعزيز السلوكيات التنظيمية الإيجابية للعاملين، وأخيرا قدمنا استنتاجا عاما حول ما تم التطرق إليه متبوعا بمجموعة من التوصيات حول الموضوع، ومن بين أهم النتائج المستخلصة بعد تفحصنا لعدد من الدراسات السابقة تبين لنا أن لرأس المال النفسي دور كبير تطوير السلوك التنظيمي الإيجابي للعاملين. كلمات دالة: رأس مال نفسي، علم نفس إيجابي، سلوك تنظيمي إيجابي. Abstract: Our Aim Through This Study Is To Shed Light On The Concept Of Psychological Capital As One Of The Modern Concepts In The Field Of Positive Organizational Behavior. We Have Tried, By Following The Steps Of The Descriptive Approach, To Provide A Definition Of The Concept Of Psychological Capital, As We Touched On Its Inception And Development, And Its Components, As Well As The Role Played By It Plays In Enhancing The Positive Organizational Behaviors Of Employees, And Finally We Presented A General Conclusion About What Was Discussed, Followed By A Set Of Recommendations On The Subject. Among The Most Important Results That Were Extracted After We Examined A Number Of Previous Studies, We Found That Psychological Capital Plays A Major Role In Developing Positive Organizational Behavior For Employees. Key Words: Psychological Capital, Positive Psychology, Positive Organizational Behavior.